2010
DOI: 10.3892/mmr.2010.369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infrasound at 8�Hz 90�dB/130�dB on NMDAR1 expression and changes in intracellular calcium ion concentration in the hippocampus of rats

Abstract: Abstract. in the present study, we investigated the effect of infrasound on the expression of n-methyl-d-aspartate (nMdar)1 as well as changes in intracellular calcium ion concentration ([ca 2+ ] i ) in the hippocampus of rats. Spraguedawley (Sd) rats were exposed for 2 h daily to infrasound at 8 Hz 90 dB or 130 dB, and nMdar1 expression was examined on days 1, 7, 14, 21 and 28. The expression of nMdar1 in the rat hippocampus upon exposure to infrasound at 8 Hz 90 dB sound pressure level (SPl) showed an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…Accumulating evidence has shown that infrasonic exposure induces abnormal ultrastructures in cortical and hippocampal neurons (6,7) and promotes blood-brain barrier permeability (5), leading to severe damage to brain tissue (16 ] i in hippocampal neurons increased following infrasonic exposure; it peaked on day 14 (90 dB), and gradually decreased to normal levels after 28 days of infrasonic exposure, suggesting a self-repairing capability occurred in the cells. A similar time-dependent pattern has also been observed in hippocampal neuron injury as described in previous studies (4,6). It has been shown that the increased expressions of 70-kDa heat-shock protein (Hsp70) and glial fibrillary acidic protein are detected following a period of infrasonic exposure, suggesting the critical role of ) at (A) 14 or (B) 28 days after infrasonic exposure was quantified by staining with Annexin V and PI.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Accumulating evidence has shown that infrasonic exposure induces abnormal ultrastructures in cortical and hippocampal neurons (6,7) and promotes blood-brain barrier permeability (5), leading to severe damage to brain tissue (16 ] i in hippocampal neurons increased following infrasonic exposure; it peaked on day 14 (90 dB), and gradually decreased to normal levels after 28 days of infrasonic exposure, suggesting a self-repairing capability occurred in the cells. A similar time-dependent pattern has also been observed in hippocampal neuron injury as described in previous studies (4,6). It has been shown that the increased expressions of 70-kDa heat-shock protein (Hsp70) and glial fibrillary acidic protein are detected following a period of infrasonic exposure, suggesting the critical role of ) at (A) 14 or (B) 28 days after infrasonic exposure was quantified by staining with Annexin V and PI.…”
Section: Discussionsupporting
confidence: 65%
“…Accumulating evidence has demonstrated that infrasound of a certain sound pressure level (SPL), usually given in decibels (dB), may lead to dysfunction of the human body (2). Moreover, exposure to infrasound has been shown to induce damage to the central nervous system (CNS) in animal models (3)(4)(5)(6). However, the underlying mechanism remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the cardiac myocytes were exposed to infrasound at 130 dB for up to 72 h. Whereas, Bao et al [20] exposed B lymphoma Raji cells to infrasound at 90 dB for only 120 min. Experimental studies have been reported that humans or various species of animals, such as rats and mice, exposed to infrasound at 90 dB and higher for short or long terms up to several months exhibited significant toxicological effects [8,21]. Why we currently used infrasound at 130 dB with the duration up to 72 h is based on the following reasons: (1) Previously, we found infrasound exposure at 130 dB significantly dysregulated the hemodynamics [8], ultrastructure [8], and L-type calcium currents [9] of cardiac myocytes and sexual behavior [5] in rats.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse influences can also cause diencephalic hypothalamic syndrome with sensor-somatic and autonomic visceral symptoms [35][36][37][38][39][40]. -adverse influence on the functions of the gastrointestinal organs, spleen and liver [41,42,43], -cause visual impairment [44]; -affects hormonal equilibrium [34,45].…”
Section: Results and Disscussionmentioning
confidence: 99%